Enhancing Drama-Script Writing through Cooperative Script: A Two-Cycle Classroom Action Study with Grade VIII.3 Students at SMP Negeri 1 Sengkang - Kadir, Abdul; Arisa, Arisa; Rahmi, Nur; Basir, Sutrisman; Rompegading, Andi Badli; Irfandi, Rizal (Tamaddun Life, 2025)
Effective creative-writing instruction demands methods that simultaneously stimulate collaboration and sharpen narrative skills. This classroom action research examined whether the Cooperative Script strategy could raise achievement in drama-script writing and increase learner engagement among 32 Grade VIII.3 students at SMP Negeri 1 Sengkang, Indonesia. Conducted during the 2021/2022 academic year, the intervention unfolded over two iterative cycles each comprising planning, action, observation, and reflection and allotted 4 × 40-minute lessons per cycle. Quantitative data were collected through individual script-writing tests scored on plot, characterization, setting, structure, and language conventions; qualitative data came from structured observation sheets that captured on-task talk and peer questioning. The class mean improved from 56.15 (pre-cycle) to 72.78 after Cycle I and reached 89.84 in Cycle II, yielding a high normalized gain (g = 0.77). Mastery levels rose from 3 % to 94 %, with only two students remaining below the minimum competency criterion of 77. Observation scores mirrored these gains, showing marked growth in reciprocal questioning and dialogic rehearsal. The findings indicate that the Cooperative Script method not only accelerates mastery of drama-writing conventions but also fosters an equitable, highly interactive learning atmosphere. Teachers seeking low-cost, student-centered approaches to creative writing may therefore adopt Cooperative Script as an evidence-based routine capable of transforming conventional lessons into collaborative workshops that amplify both cognitive and social outcomes.